Bridging mental boundaries in a postcolonial microcosm : identity and development in Vanuatu - Miles, William F. S. (Honolulu : University of Hawaiì Press, 1998)
The South Pacific archipelago of Vanuatu simultaneously experienced the two major types of colonialism of the modern era (British and French), the only instance in which these colonial powers jointly ruled the same people in the same territory over an extended period of time. This, in addition to its small size and recent independence (1980), makes Vanuatu an ideal case study of the clash of contemporary colonialism and its enduring legacies. At the same time, the uniqueness of Melanesian society highlights the singular role of indigenous culture in shaping both colonial and postcolonial political reality. With its close attention to global processes, Bridging Mental Boundaries in a Postcolonial Microcosm provides a fresh comparative approach to an island state that has most frequently been examined from an ethnographic or area studies perspective. William F.S. Miles looks at the long-term effects of the joint Franco-British administration in public policy, political disputes, and social cleavages in post-independence Vanuatu. He emphasizes the strong imprint left by "condocolonialism" in dividing ni-Vanuatu into "Anglophones" and "Francophones," but also suggest how this basic division is being replaced (or overlaid) by divisions based on urban or rural residence, "traditional" or "modern" employment, and disparities between the status and activities of men and women. As such, this volume is more than an analysis of a unique case of colonialism and its effects; it is an interpretation of the evolution of an insular society beset by particularly convoluted precolonial, colonial, and postcolonial fractures. Based principally on research conducted in 1991 and, following a key change in Vanuatu's government, a subsequent visit in 1992, the analysis is enriched by regular comparisons between Vanuatu and other colonized societies where the author has carried out original research, including Niger, Nigeria, Martinique, and Pondicherry. Extensive interviews with ni-Vanuatu are integrated throughout the text, presenting islanders' views of their own experience
Frontmatter -- Contents -- List of Maps, Tables, and Figures -- Foreword -- Preface: Choosing Vanuatu -- Introduction Boundaries, Juridical and Mental -- Chapter 1. Mental Rivalries and Condocolonialism -- Chapter 2. Nationalism, Kastom, and Other Boundaries of Identity -- Chapter 3. Religious Boundaries Constructed and Bridged -- Chapter 4. Language, Education, and National Identity -- Chapter 5. New Boundaries in Space, Time, Law, Gender, and Race -- Chapter 6. Global Boundaries in the Microcosm -- Appendix A: Excerpts from the Convention Establishing the New Hebrides Condominium -- Appendix B: Excerpts from the Constitution of the Republic of Vanuatu -- Persons Interviewed -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 213-255) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Vanuatu -- History; Postcolonialism -- Vanuatu; Nationalism -- Vanuatu; National characteristics, Vanuatuan; Postcolonialisme -- Vanuatu; Nationalisme -- Vanuatu; HISTORY; SOCIAL SCIENCE -- Anthropology -- Cultural; Nationalism; Postcolonialism; Vanuatu; Nationalismus; Entkolonialisierung; Sozialer Konflikt; Vanuatu; Nationale identiteit; Postkolonialisme; Nationalisme -- Vanuatu; Postcolonialisme; Vanuatu -- Histoire; Vanuatu -- Influence coloniale; Humaniora -- Historie; History